The inﬂuence of the internal factors on the resolution of the Colombian armed conﬂict and the result of the 2016 peace talks - Maria Seredá (Ибероамериканские тетради)
The article analyses three basic themes in the peace negotiations between the government of Colombia and the FARC: agrarian question, political participation and drug-traﬃcking. The article deals with the state of these problems presented in the historic perspective and with some variants of its resolution included into the Final agreement with the FARC. The author attempts to evaluate these agreements and to explain the declining of the agreement in the referendum (2016) for its approval.